Highly Selective Tandem Photoelectrochemical C-H Activation via Bromine Evolution Reaction in Two-Phase Electrolyte - Chae, Sang Youn; Mehmood, Adeel; Park, Eun Duck (Journal of the American Chemical Society, 2024)
The development of environmentally friendly and safe chemical processes using renewable energy sources is important. In this study, a photoelectrochemical (PEC) cell was used for the tandem bromination of sp3 carbon within a unique two-phase electrolyte system. By incorporation of a RuOx cocatalyst, the Ta3N5 photoelectrode demonstrated a remarkable selectivity for Br2 close to 100%. The kinetic study for charge carriers of photoelectrodes reveals that the improved charge transfer at Ta3N5/RuOx interfaces contributed to excellent photoelectrochemical Br2 evolution activity. The photoelectrochemically produced Br2 was utilized for bromination of α-sp3 carbon in toluene, 1-methylnaphthalene, ethylbenzene, or cyclohexane by the Ta3N5/RuOx photoanode with 100% regioselectivity. The coupling of the Ta3N5 photoanode and InP photocathode generated H2 and Br2 under light illumination without external bias. This study provides systematic insights into the design of photoelectrodes for solar-driven tandem bromination systems within the unique environment of a two-phase electrolyte system.
Keywords: Cell/B.E; Chemical process; Electrolyte systems; Evolution reactions; Photo-anodes; Photoelectrochemicals; Photoelectrode; Renewable energy source; Safe chemicals; Two phase